A Vocation Receptive to Outside Influences: Doctors, Hospitals and Medicine in Lusignan and Venetian Cyprus, 1191–1570. (31st December 2021) - Coureas, Nicholas
Abstract: In this article the presence and activities of doctors in Cyprus throughout the Lusignan and Venetian periods and the extent to which these were influenced by Western Europe, the Latin East and the Muslim world will be assessed and evaluated. The records for the presence of doctors are diverse, and include papal documents, the proceedings of provincial synods of the Latin Church, Venetian and Genoese notarial deeds of the thirteenth to the fifteenth centuries, legal texts, chronicles, and royal fiscal records. Despite this diversity of records, the information they provide presents imbalances. Considerable information is available on the different types of doctors active on the island, including veterinary surgeons, and less on the hospitals and how they functioned, or on the practice of medicine itself, even though some valuable items of information are found concerning these last two areas. In terms of ethnic and cultural origins it is clear from the available information that, even if most of the doctors recorded are of Western origin, Jewish and Muslim doctors were held in high regard, despite the injunctions of the island's Latin Church against visiting doctors who were not of the Christian faith.